2019
DOI: 10.1111/apt.15157
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: mycophenolate mofetil as a second‐line therapy for autoimmune hepatitis

Abstract: Background: First-line treatment for autoimmune hepatitis (AIH) typically includes corticosteroids in combination with azathioprine. Mycophenolate mofetil (MMF) is often used as a rescue therapy in patients who are intolerant of, or nonresponsive to, standard therapy. Aim:To systematically review studies and perform a meta-analysis on the efficacy and safety of MMF as a second-line therapy for AIH patients.Methods: MEDLINE, EMBASE and Cochrane Central were searched for studies that reported data on efficacy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 35 publications
2
51
0
Order By: Relevance
“…MMF has been given to patients with AIH who are intolerant of AZA or have an incomplete response or treatment failure with glucocorticoid/ AZA. In a meta-analysis involving five studies and 309 patients, (425) the pooled overall response rate was 58% (82% for AZA intolerance and 32% for treatment failure). MMF-based therapies were well tolerated, with a pooled adverse event rate of 14%, leading to discontinuation in 8%.…”
Section: Mmfmentioning
confidence: 99%
“…MMF has been given to patients with AIH who are intolerant of AZA or have an incomplete response or treatment failure with glucocorticoid/ AZA. In a meta-analysis involving five studies and 309 patients, (425) the pooled overall response rate was 58% (82% for AZA intolerance and 32% for treatment failure). MMF-based therapies were well tolerated, with a pooled adverse event rate of 14%, leading to discontinuation in 8%.…”
Section: Mmfmentioning
confidence: 99%
“…Recent systematic reviews demonstrated the overall efficacy of MMF as second-line therapy in AIH, with a low discontinuation rate due to side effects. 48,49 Other second-line treatments used by experts include tacrolimus and cyclosporine, and sirolimus, infliximab, and rituximab. 45 Since B-cells play a significant role in the pathogenesis of AIH, B cell depletion is a promising strategy for the management of AIH.…”
Section: Second-line Medical Treatmentmentioning
confidence: 99%
“…Due to the potential for negative health outcomes associated with antepartum and postpartum flares, it is important that AIH activity is monitored closely and is well controlled before and during pregnancy and in the early postpartum period. Standard AIH treatment consists of corticosteroids and azathioprine, although it is noted that mycophenolate mofetil is an acceptable alternative agent if standard therapy is not tolerated . Despite the lack of meta‐analyses and systematic reviews on AIH therapy in pregnancy, observational data about the use of corticosteroids and azathioprine in other immunologic diseases support the use of these therapies in AIH .…”
Section: Primary Liver Diseases That Are Concurrent With Pregnancymentioning
confidence: 99%